EARLY WEANING IN A BASIC HEALTH UNIT IN CEARÁ (Cadernos ESP, 2023)
To identify the factors contributing to the interruption of exclusive breastfeeding in babies younger than 6 months. Qualitative study focused on the content analysis of the participants' statements. The research was carried out in a Basic Health Unit (UBS) located in the Sertão Central region, in the municipality of Quixeramobim-CE. In addition to the interview, socioeconomic and obstetric data were collected through a semi-structured interview composed of open questions and self-composed questions. The reasons identified in the speeches during the interviews that contributed to early weaning were: maternal work; breast engorgement and cracked nipples; persistent baby crying and “weak milk” and; interference from family or close people. The main factors that influenced mothers to carry out early weaning were the return to the labor market, breast engorgement and cracked nipples, persistent baby crying and “weak milk” and, family interference or close people.
Keywords: Breastfeeding; Family Health Strategy; NURSING; Prenatal Care